The substantiation of the optimum type of the machine for the aggregation with the tillage sowing complex - Kushnarev, Artur; Кушнарьов, Артур Сергійович; Кушнарев, Артур Сергеевич; Serbiy, Vitalij (Tavria state agrotechnological university, 2017)
The method for the optimum power determination and material capacity of a tractor for a specific width of the tillage sowing complex and a given field area is given in the article. The recommendations on the compilation of machine-tractor units in the composition of the tillage sowing complex are given.
Keywords: machine; tractor; complex; tillage; sowing